Preimplantation genetic diagnosis/screening by comprehensive molecular testing. (14th July 2015) - Kurahashi, Hiroki; Kato, Takema; Miyazaki, Jun; Nishizawa, Haruki; Nishio, Eiji; Furukawa, Hiroshi; Miyamura, Hironori; Ito, Mayuko; Endo, Toshiaki; Ouchi, Yuya; Inagaki, Hidehito; Fujii, Takuma
Abstract: Although embryo screening by preimplantation genetic diagnosis (PGD) has become the standard technique for the treatment of recurrent pregnancy loss in couples with a balanced gross chromosomal rearrangement, the implantation and pregnancy rates of PGD using conventional fluorescence in situ hybridization (FISH) remain suboptimal. Comprehensive molecular testing, such as array comparative genomic hybridization and next‐generation sequencing, can improve these rates, but amplification bias in the whole genome amplification method remains an obstacle to accurate diagnosis. Recent advances in amplification procedures combined with improvements in the microarray platform and analytical method have overcome the amplification bias, and the data accuracy of the comprehensive PGD method has reached the level of clinical laboratory testing. Currently, comprehensive PGD is also applied to recurrent pregnancy loss due to recurrent fetal aneuploidy or infertility with recurrent implantation failure, known as preimplantation genetic screening. However, there are still numerous problems to be solved, including misdiagnosis due to somatic mosaicism, cell cycle‐related background noise, and difficulty in diagnosis of polyploidy. The technology for comprehensive PGD also requires further improvement.